Click chemistry-enabled gold nanorods for sensitive detection and viability evaluation of copper(II)-reducing bacteria - Tongtong Tian; Wenjing Yang; Xiaohuan Wang; Te Liu; Baishen Pan; Wei Guo; Beili Wang (Materials Today Bio)
The rise of antibiotic resistance poses a significant and ongoing challenge to public health, with pathogenic bacteria remaining a persistent threat. Traditional culture methods, while considered the gold standard for bacterial detection and viability assessment, are time-consuming and labor-intensive. To address this limitation, we developed a novel point-of-care (POC) detection method leveraging citrate- and alkyne-modified gold nanorods (AuNRs) synthesized with click chemistry properties. These AuNRs exhibit superior biocompatibility and enhanced quantitative performance compared to conventional surfactant-modified AuNRs. Our method, termed AuNRs–bacteria-initiated click chemistry (AuNRs–BICC), detects CuII-reducing bacteria by quantifying AuNRs bound to a biosensing interface via bacteria-mediated CuII reduction to CuI and subsequent click chemistry with biosensing interface of azide modifications. Using dark-field microscopy (DFM), we demonstrated a strong linear correlation between AuNR counts and the logarithm of bacterial concentration for both Gram-negative Escherichia coli (including KPC-2-expressing antibiotic-resistant strains) and Gram-positive Staphylococcus aureus across a range of 101 to 107 cells, achieving a remarkable detection limit of 101 cells. The AuNRs–BICC biosensor exhibits high selectivity for target bacterial strains and provides rapid detection within 3 h. Furthermore, it can assess bacterial viability in the presence of various antibiotics, including meropenem, ceftriaxone and tetracycline, suggesting its potential for rapid antibiotic susceptibility testing and facilitating timely clinical intervention for infectious diseases.